Η σπασμωδική συγκριτική γραμματολογία του νέου ελληνισμού και η "Γραικοτουρκική" διασκευή του πολυπαθούς του Γρ.Παλαιολόγου - Κεχαγιόγλου, Γιώργος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1995)
The article deals with some aspects of the 19th c. fortunes of the Modem Greek picaresque novel Ό Πολύπαθης (The Much-Suffering/The Much-Tried, Athens 1839). Written by Gregorios Palaiologos, a Greek born in Constantinople and active particularly in France and the Greek State, the novel gained its justified fame especially through its four-volume «Greco-Turkish» («karamanh») adaptation by Evangelinos Misaelides (Ταμασάϊ Δοννγιά βε Αζεφακιάρ-ον Λζεφακές / Tamasa-i Diinya ve Cefakâr u Cefakes = The Spectacle of the World. The Torturer and the Tortured, Constantinople 1871-2). The original Greek work went almost unnoticed in Athens at the time and was only recently «rediscovered » by Modern Greek editors and comparatists; yet Misaelides, a leading figure in «Greco-Turkish» literature and a well-known translator, editor and publisher in Smyrna and Constantinople managed to transform Palaiologos’ novel into an influential and very popular work that combines the technique of a frame story with inserted anecdotes, apologues and a rich gamut of mythological, historical, religious and ecclesiastical, and anthropological material. Believed for a long time as being an original work, and the first Modern Turkish novel as well, Temasa-î Diinya was repeatedly praised by turcologists, reedited recently in Istanbul in the Moden Turkish (romanized) alphabet and studied either as a piece revealing interesting linguistic features of the Ottoman Turkish of the time or as an evidence of a pro-Ottoman literary movement embraced by the Turkish-speacking Orthodox Christian élite supposedly fully integrated into the Ottoman «tradition» and the so-called Ottoman polysystem. The author points out a lot of misunderstandings and misconceptions and discusses some prejudices both of Turkish and Greek scholars. In his opinion, Misaelides’ profound knowledge of the ancient, medieval and Modem Greek language and literary tradition, as well as his awareness of contemporary Western European (mainly French) literary trends should not be questioned; in matters of intertextuality, a much greater range of Modern Greek literary texts (including the novelistic Apocrypha, from the mid 19th c. onwards) should be investigated as an eventual parallel set of sources of this «Greco-Turkish» masterpiece.